2018
DOI: 10.14444/5043
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association With Spino-Pelvic Relationships and Clinical Outcome of Type A Thoracic and Lumbar Fractures Treated Non-Surgically?

Abstract: Background: The objective was to evaluate if there is an association of the spino-pelvic relationships and the global spinal alignment with the outcome of AO type A injuries treated nonsurgically. Methods: This is a retrospective case series. Patients treated nonsurgically for AOSpine type A fractures (T1-L5) with at least 1 year follow-up identified. A standing antero-posterior and lateral 36-inch radiographs and measures of spino-pelvic relationships and sagittal alignment were obtained, as well as clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
0
6
0
4
Order By: Relevance
“…7 Pain and some degree of disability may persist in some cases. 10 Comparative studies randomizing operative and nonoperative stable injuries are necessary to evaluate the benefits of pain control and the level of disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Pain and some degree of disability may persist in some cases. 10 Comparative studies randomizing operative and nonoperative stable injuries are necessary to evaluate the benefits of pain control and the level of disability.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] However, some patients may still have chronic pain after the treatment of these fractures, despite being mechanically stable. 10 Neurological Deficits (Radicular -N2, Incomplete -N3 and Complete -N4)…”
Section: Neurologically Intact (N0 and N1)mentioning
confidence: 99%
“…For example, one study found that it accurately predicted treatment 99% of nonoperative cases, but it only accurately predicted treatment in 46.6% of patients in the operative treatment group. 27 The main drawback of this system is that it relies on interpretation of stability of the posterior ligamentous complex on MRI, which inherently varies between surgeons. The AOSpine thoracolumbar classification attempts to simplify fracture classification and guide treatment by creating hierarchical, morphologic criteria.…”
Section: Thoracolumbar Spinementioning
confidence: 99%
“…[5][6][7][9][10][11] No entanto, poucos estudos analisaram parâmetros espinopélvicos globais dos pacientes com FTE. 12,13 Nossa hipótese é que o alinhamento espinopélvico de indivíduos que tiveram FTE esteja alterado em relação à população assintomática em razão do aumento da CTL.…”
Section: Introductionunclassified